Tinjauan Kriminologis terhadap Aksi Premanisme di Pelabuhan Tenau Kupang - Yannita Nilam Herman; Jimmy Pello; Darius Kian (Pusat Riset dan Inovasi Nasional, 2024)
This study examines is criminological review of acts of thuggery at Tenau Port, Kupang. This research uses empirical juridical research, or what is called field research, namely examining applicable legal provisions and what happens in reality in society.. The results of this research show: (1) The form of crime of thuggery referred to in the discussion and scope of this research is generally what is known as harassment committed by unscrupulous drivers against ship passengers with various modus operandi. The modus operandi in acts of thuggery that has been researched and occurred factually at Tenau Harbor in its scope and which occurs most often is threats carried out by several rental or car rental drivers by forcefully demanding money from ship passengers and drivers who threaten passengers asking for money. to get into his car. (2) The efforts of the Kupang City Police in dealing with acts of thuggery at Tenau Port, Kupang: Thugism, Modus Operandi, Countermeasures.